Internal and external factors that affect scientific Research in postgraduate students - Sobero Rodríguez , Fany Yexenia (2024)
During postgraduate studies included in master's and doctoral programs, there are various factors that have a positive or negative influence on students during the development of research work leading to the formulation of their thesis projects. The objective of this article is to carry out a review of these factors which have been identified by various authors, for this a review process was carried out in various databases selected specialized literature on educational and psychological topics within the period from 2018 to 2022, as a result of this review it was possible identify the most significant factors that are considered to influence the scientific research of graduate students, which were classified as internal factors (motivation, writing skills, academic identity, self-esteem, self-efficacy) that are associated with the students and external factors (supervision ), personal/social life, departmental structures, financial opportunities) associated with the context.